Writing & publishing peer-reviewed scientific journal articles - Yin, Chun-Yang (Penerbit Universiti Teknologi Mara, 2010)
This book is intended to provide university students and entry-level academics a basic, practical and step-by-step guide to writing and publishing such journal articles.